Pengaruh Citra Merek Dan Reputasi Perusahaan Terhadap Loyalitas Pelanggan Pada Agen Jne Gang Nangka Kota Depok - Depi Herlianti; Rosa Lesmana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. reputation on customer loyalty at the JNE Agent located on Gang Nangka, Depok City. The research employed a quantitative method with an associative approach. Research data were collected through the distribution of questionnaires to 99 respondents who were JNE customers, using an accidental sampling technique. Data analysis was conducted using SPSS version 30, which included descriptive statistical analysis, research instrument testing, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing using t-tests and F-tests. The results indicate that, partially, brand image has a significant effect on customer loyalty with a coefficient of determination of 73.1%. Corporate reputation also partially has a significant effect on customer loyalty with a coefficient of determination of 84.6%. Simultaneously, brand image and corporate reputation have a significant effect on customer loyalty with a coefficient of determination of 85.3%. The hypothesis testing results show that all research hypotheses are accepted.